Deprescription in the polymedicated elderly. A reflexive look at the Cuban context - Alicia del Rosario Ramírez Pérez (Revista Habanera de Ciencias Médicas, 2020)
Introduction: The excessive therapeutic interventionism promotes polypharmacy and prescription errors in the elderly. In Cuba, the polymedicated elderly is a recurrent problem; however, the information about prescription has a limited diffusion in the scientific field. Objective: To describe the current knowledge about deprescription and the need for a strategy aimed at addressing the problem of the polymedicated elderly in Cuba. Material and Methods: An extended review based on the authors’ expertise was carried out from 2003 to 2020. The search and selection criteria and the access to databases and sources indexed in Cochrane Library, SciELO, Lilacs, PubMed, Hinari, MEDLINE, ScienceDirect, and Elsevier allowed us to cite 54 research works (70% updated).  The final document was written on the basis of qualitative research methodology and historical-logical and analysis-synthesis approaches. Development: The term “deprescription” appeared in 2003 to solve the problem of polypharmacy.  It is a quaternary prevention tool that involves dismantling medication treatment with various nuances. Its rise revolutionized different work currents worldwide. Adequate scientific evidences of its need and opportunity for the best pharmacotherapeutic management in the elderly justify a design and implementation that takes into account the social determinants of each country. Some elements are suggested for the definition; the importance of geriatric pharmacology is affirmed in the face of intervention designs. Conclusions: Deprescription is an inherent process of pharmacotherapeutic decisions in elderly patients attended in advanced healthcare systems. It shows a reduction of mortality, prescription of drugs and inappropriate prescriptions. The National Drug Program does not have guidelines for its implementation; therefore, to develop a strategy will be a challenge for the Cuban Public Health.